Penerapan Model Pembelajaran Snowball Throwing Dalam Upaya Meningkatkan Pengetahuan Siswa Kelas VII Di SMP Islam Yapkum Depok - Mufida Hyifa (Institut Agama Islam Sahid (INAIS) Bogor, 2023)
The results of interviews and observations conducted by researchers at Yapkum Islamic Junior High School show that grade VII students have not been able to use their knowledge as well as possible in the learning process. This is caused by students who do not know how to develop and improve the knowledge they have, and the selection of learning models carried out by teachers is too monotonous. The purpose of this study is to determine the application of the Snowball Throwing learning model in an effort to increase student knowledge. This study used a type of classroom action research. The object in this study was 28 Class VII students. Data collection using test assessment instruments, practices, and instruments owned by teachers. Based on student learning outcomes after using the Snowball Throwing learning model experienced a significant increase of 28.5% for original ideas, an increase of 22.1% for the correctness of concepts, and an increase of 8.8% for the accuracy of using terms.